Reflective Feedbacks and Project-Based Activities to Improve the Students’ Writing Skill: An Exploratory Action Research - Sukmawati, Nur Najibah (UIN Salatiga, 2020)
Teaching writing to Informatics Engineering students has its uniqueness when it comes to what specific issue(s) the students are facing and how to cope with them. This study aims at finding out some feedback for the author’s previous teaching practices in writing a descriptive text which becomes the basis to give an exact intervention as well as to find out whether the intervention is able to improve the students’ skills in writing a descriptive text. This is exploratory action research to the 30 students of the third semester in the Informatics Engineering study program of a private university in Indonesia. To gain feedback on the previous instructional practices, a senior colleague is invited as a consultant and an open-ended questionnaire was distributed to the students. Some issues were found. After a deep discussion with the senior colleague, it is concluded that project-based activities could cope with the issues. To prove it, a writing test and open-ended interview were conducted. During the instructional practices, a collaborator was invited to observe using an observation sheet. The result revealed that project-based activities engaged the students and directed them in accomplishing the task. The test also showed improvement in students’ average scores. These findings proved that implementing project-based activities can improve the students’ skills in writing a descriptive text. Keywords: Exploratory Action Research, Reflective Feedbacks, Project-Based Activities